Pengaruh Kapabilitas Branding dan Tanggung Jawab Sosial Perusahaan terhadap Loyalitas Pelanggan yang dimediasi oleh Kepuasan Pelanggan - Fathorrahman Fathorrahman; Ummi Wahyuni; Zainurrafiqi Zainurrafiqi; Runik Puji Rahayu; Devi Lestari Pramita Putri; Nurul Hidayati (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to analyze the effect of branding capability and corporate social responsibility on customer loyalty, with customer satisfaction as a mediating variable, among religious tourism visitors in Madura. The background of this study is based on the importance of strong branding strategies and the implementation of corporate social responsibility in creating positive customer experiences, particularly in the context of value-based religious tourism. This study uses a quantitative approach with a survey method, involving 150 tourists as the sample. Data collection was conducted through a Likert-scale-based questionnaire, which was then analyzed using path analysis to examine the relationships between variables. The results show that branding capability and corporate social responsibility have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction was found to have a significant effect on customer loyalty. Another finding indicates that the effect of branding capability and corporate social responsibility on customer loyalty is significantly mediated by customer satisfaction. These findings provide practical implications for the management of religious tourism destinations in Madura to strengthen branding elements and social commitment to enhance customer satisfaction and loyalty sustainably..